U.S. regional deterrence strategies - Watman, Kenneth, 1948-; Wilkening, Dean, 1950-; Arquilla, John.; Nichiporuk, Brian, 1966-; Arroyo Center. Strategy and Doctrine Program; Project Air Force (U.S.). Strategy, Doctrine, and Force Structure Program; Rand Corporation; United States. Army.; United States. Air Force (Santa Monica, CA : RAND, 1995)
This report assesses the requirements of a deterrence strategy for application to potential regional adversaries. The authors argue that states content with their status quo (e.g., the former Soviet Union during the Cold War) should be relatively easy to deter, especially from seeking gain, because they are likely to be risk-averse decisionmakers. On the other hand, many regional adversaries, already dissatisfied with the status quo and anticipating further losses, can be hard to deter, though not impossible. Hence, the U.S. military problem of regional deterrence in this instance boils down to two factors: (1) how the United States can make its deterrent threats highly credible; and (2) what military capabilities are required for credible denial and punishment threats. Should an adversary be willing to take high risks, the authors suggest that the United States adopt a national military strategy based on the ability to deny the opponent's political/military objective, either by basing U.S. forces within the region in times of crisis or by convincing the adversary that they can be forward deployed rapidly if the need arises.
"RAND Arroyo Center."
"RAND Project Air Force."
"This research was conducted jointly under the Strategy, Doctrine, and Force Structure Program of Project Air Force and under the Strategy and Doctrine Program of the Army Research Division's Arroyo Center"-Pg. IV.
Includes bibliographical references (p. 99-106).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Deterrence (Strategy); United States -- Military policy